Assessing Critical Thinking in English Language Teaching: A Document Analysis of Student Book Reviews - Fahmy Imaniar (Universitas Muhammadiyah Jember, 2024)
Much like problem-solving and decision-making skills as needed in the 21st century, critical thinking is an essential skill in English Language Teaching (ELT), as its demands students to analyze, evaluate, and articulate logical arguments. Even with its noted significance, the planning and the evaluation of critical thinking components within ELT remains difficult because of the absence of systematic assessment instruments. The purpose of this study is to evaluate the critical thinking levels of English Language Education Department students through documents analysis of 34 first-drafted book reviews that were analyzed using the OECD Critical Thinking Assessment Rubric. The rubric assesses learners’ ability to take a personal stance, consider opposing views, provide sufficient evidence, and identify claims and limitations. The result shows that 17.6% of students had Outstanding critical thinking skills, 29.4% Flourishing, 35.3% Emergent, and 17.6% Dormant. Most students were able to formulate an argument, but justifications and consideration of other perspectives were inadequately resolved at the shallow level. The results from this study indicate the importance of providing follow-up action of students’ writing for critical thinking and defined criteria for critical thinking assessments in ELT writing classes. This investigation has added the literature on critical thinking evaluation in ELT.